O capital e seu espaço. Para além de produzir valor e espaço, o capital produz o desenvolvimento geográfico desigual - Sandra Lencioni (Confins)
Capital produces different forms of spatiality. This comprehension allows us to understand uneven geographical development within the production of space. We consider the production of two commodities for exportation as an analytical reference in order to discuss the process of capital accumulation in relation with the production of space. Following, we approach the current hegemony of financial capital, trying to update historically the production of different forms of spatialization of value production. This discussion distinguishes between the processes of valorization and capitalization. It aims to state that the dominance of finance can be interpreted as a new regime of capital accumulation, namely the regime of property accumulation, which affirms property and its income. Within this regime, what matters is share yield, that is, how much can they can return. We take industry as an issue to debate, seen from the perspective of belonging or not to a financialized economic group. Therefore, we take into account a stronger or weaker link with the process of capitalization, and we make considerations on the relation between industry and territory, as well as the production of spatialities that are either more lasting or more ephemeral.